BGAL1 depletion boosts the level of β‐galactosylation of N‐ and O‐glycans in N. benthamiana. Issue 7 (11th January 2020) - Kriechbaum, Ricarda; Ziaee, Esmaiel; Grünwald‐Gruber, Clemens; Buscaill, Pierre; van der Hoorn, Renier A. L.; Castilho, Alexandra
Summary: Glyco‐design of proteins is a powerful tool in fundamental studies of structure–function relationship and in obtaining profiles optimized for efficacy of therapeutic glycoproteins. Plants, particularly Nicotiana benthamiana, are attractive hosts to produce recombinant glycoproteins, and recent advances in glyco‐engineering facilitate customized N ‐glycosylation of plant‐derived glycoproteins. However, with exception of monoclonal antibodies, homogenous human‐like β1, 4‐galactosylation is very hard to achieve in recombinant glycoproteins. Despite significant efforts to optimize the expression of β1, 4‐galactosyltransferase, many plant‐derived glycoproteins still exhibit incomplete processed N ‐glycans with heterogeneous terminal galactosylation. The most obvious suspects to be involved in trimming terminal galactose residues are β‐galactosidases (BGALs) from the glycosyl hydrolase family GH35. To elucidate the so far uncharacterized mechanisms leading to the trimming of terminal galactose residues from glycans of secreted proteins, we studied a N. benthamiana BGAL known to be active in the apoplast ( Nb BGAL1). Here, we determined the Nb BGAL1 subcellular localization, substrate specificity and in planta biological activity. We show that Nb BGAL1 can remove β1, 4‐ and β1, 3‐galactose residues on both N‐ and O ‐glycans. Transient BGAL1 down‐regulation by RNA interference (RNAi) and BGAL1 depletion by genome editing drastically reduce β‐galactosidase activity in N. benthamiana and increase the amounts of fully galactosylated complex N ‐glycans on several plant‐produced glycoproteins. Altogether, our data demonstrate that Nb BGAL1 acts on galactosylated complex N ‐glycans of plant‐produced glycoproteins.